A new endoscopic technique for specific gastrointestinal stromal tumors: a retrospective cohort study. (2nd November 2021) - Hu, Junbi; Ren, Mudan; Zhao, Yan; Lu, Guifang; Lu, Xinlan; Yin, Yan; Zhao, Qian; She, Junjun; He, Shuixiang
Abstract: Objectives: Surgical resection is recommended for treating gastrointestinal stromal tumors (GISTs) >20 mm. With the emergence of minimally invasive concept, endoscopic techniques are involved. We introduce a new endoscopic technique termed as endoscopic submucosal resection preserving serosa (ESR-PS) for GISTs ≥ 20 mm with mucosal erosion or ulcer locating at deep muscularis propria. Methods: This retrospective cohort study collected patients at the endoscopy center of the First Affiliated Hospital of Xi'an Jiaotong University between January 2019 and 2021. The primary outcome was adverse events including pneumoperitoneum, fever and delayed bleeding. The second outcomes included en bloc resection complete en bloc resection, recurrence, operation time, hospital stay time after ESR-PS, postoperative indwelling gastric tube and postoperative eating. Results: A total of 49 patients were included. One patient experienced pneumoperitoneum. All patients did not experienced fever or delayed bleeding after ESR-PS. All cases achieved en bloc resection and complete en bloc resection. The median operation time of ESR-PS was 49 min (range 43–71). The indwelling gastric tubes were given to patients for 1 d or 2 d after ESR-PS. After 1 d or 2 d, patients started oral diet, staying in hospital for a median of 4 (3–4) d after ESR-PS. During the follow-up time, recurrence was not found. Conclusions: Our study indicated that ESR-PS is a feasible, effective and safe technique for GISTs ≥ 20mm with mucosal erosion or ulcer locating at deep muscularis propria. More large, multi-center and prospective studies are needed to evaluate the effectiveness and safety of ESR-PS in the future.